Emerging Sanitizers: An Alternative in the Postharvest of Arugula - Inestroza-Lizardo, Carlos; Escalona, Victor Hugo (Agrociencia Uruguay, 2015)
The aim of this work was to evaluate the effect of chlorine dioxide (3 and 5 mg L-1; ClO2 3 and ClO2 5), peroxide hydrogen (30 and 50 mg L-1; H2O2 30 and H2O2 50) and UV-C radiation (4 and 5 KJ m-2; UV 4 and UV 5) on the respiration rate, color and microbiological load of arugula leaves (Eruca vesicaria), stored eight days under a passive modified atmosphere at 5 °C; and to compare them with sodium hypoclorite 100 mg L-1; (NaClO 100). After the harvest, the leaves of arugula were transported from the field and stored for 24 h in a chamber at 5°C. The processing was carried out at 8 °C, where the leaves were washed by immersion for 3 min in potable water, before being subjected to different treatments. The microbiological quality was clearly influenced by the sanitizers evaluated. ClO2 5 and H2O2 50 decreased the enterobacteria counts in 1.3 log CFU g-1 compared to the raw material, while NaClO, ClO2 5 and H2O2 50 were the most effective delaying the aerobic mesophilic bacteria, decreasing the counting between 1.0 and 1.4 log CFU g-1. Unlike NaClO, ClO2 also reduced the load of psychrophile microcoorganisms. All treatments preserved the color of the leaves. These results suggest that ClO2 and H2O2 can be used as an alternative to NaClO in the postharvest washing of arugula leaves considering microbiological quality and green color during refrigerated storage.